Mounting bracket - Sahari, Barkawi (2009)
A mounting structure for a gaseous fuel system such that it can be accommodate fuel piping and gas tanks in in-line direction with all tanks mounted underneath the platform supported by means of a front tank mounting bracket and a front tank mounting strap fitted to the front tank mounting bolt and the gas tanks are arranged for ease of assembly, disassembly, maintenance, inspection, service and replacement of cylindrical gas tanks.